The Penetration Depth Of Weld Metal In Underwater Welding With Variations In Water Depth And Water Flow Velocity - Fajar Paundra; A. Juan; Triyono Triyono; P. Elmiawan; P. Yunesti (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2021)
Underwater wet welding (UWW) is widely used in the repair of offshore construction and underwater pipelines using the Shielded Metal Arc Welding (SMAW) method. This research was conducted to see the effect of flow (0 m/s, 1 m/s, and 2 m/s) and water depth (2.5 m and 5 m) on the depth weld metal penetration of the SS400 steel underwater welded joints. The control variables used were welding speed of 1.5 mm/s, current of 90 A, electrode E6013 (RB26) with a diameter of 4 mm, type of negative electrode polarity (DC), spraying distance of 10 cm, the direction of spraying in the opposite direction of welding, and fresh water. The results showed that the deeper and fast the flow velocity would decrease the depth of penetration and increases porosity. This is due to the decreased transferability of the molten metal during the welding process.